COOPERATIVE INTEGRATED READING AND COMPOSITION (CIRC) MODEL TO IMPROVE THE WRITING SKILLS OF CLASS V STUDENTS IN ELEMENTARY SCHOOLS INPRES ENDE 14 - Yohana Nono BS; Maria Finsensia Ansel (Sean Institute, 2023)
The problem in this study is the application of the Cooperative Integrated Reading and Composition (CIRC) model in improving students' writing skills and to improve writing skills through the use of the CIRC model in SDI Ende 14 students. The research objective was to determine the application of the CIRC model in improving students' writing skills. students and to find out writing skills through the use of the CIRC model on SDI Ende 14 students. The type of research used was classroom action research (CAR) with a qualitative approach. Collecting research data using observation techniques, tests, interviews, and documentation. The results of this study indicate that learning using the CIRC model can involve students so that students can also play an active role in the learning process and student learning outcomes in writing skills using the CIRC model increase. This is shown by the increase in the average value of writing skills using the CIRC model where the average value of the first cycle of writing skills is 62.96 and the average of the second cycle of writing skills is 90.50.